Rawlsian Contractualism and Healthcare Allocation: A response to Torbjörn Tännsjö (Diametros, 2021)
The consideration of the problem of healthcare allocation as a special case of distributive justice is especially alluring when we only consider consequentialist theories. I articulate here an alternative Rawlsian non-consequentialist theory which prioritizes the fairness of healthcare allocation procedures rather than directly setting distributive parameters. The theory in question stems from Rawlsian commitments that, it is argued, have a better Rawlsian pedigree than those considered as such by Tännsjö. The alternative framework is worthy of consideration on its own merits, but it also casts light on two related difficulties with Tännsjö’s approach: (i) the limits of his supposedly ecumenical methodology, which is revealed to be dialectically suspect and (ii) issues with the type of abstraction and idealization from actual judgements and preferences which the approach requires.